Effect of Serum 25-Hydroxyvitamin D on Risk for Type 2 Diabetes May Be Partially Mediated by Subclinical Inflammation: Results from the MONICA/KORA Augsburg study - Thorand, Barbara (American Diabetes Association, 2011)
OBJECTIVE: To assess the association between serum 25-hydroxyvitamin D (25-OHD) and incident type 2 diabetes and to determine whether the association is mediated by subclinical inflammation. RESEARCH DESIGN AND METHODS: Using a case-cohort design, baseline levels of 25-OHD were measured in 416 case subjects with incident type 2 diabetes and 1,267 noncase subjects selected from a source population of 7,936 middle-aged participants in the population-based Monitoring of Trends and Determinants in Cardiovascular Disease (MONICA)/Cooperative Health Research in the Region of Augsburg (KORA) study. RESULTS: A significant inverse association was observed between serum 25-OHD and incident type 2 diabetes after adjustment for diabetes risk factors and season. The hazard ratio (HR) and 95% CI comparing tertile extremes was 0.63 (0.44–0.90) (P(trend) = 0.010). Further adjustment for C-reactive protein, interleukin-6, soluble intercellular adhesion molecule-1, and interferon-γ–inducible protein-10 attenuated this association by 16% (HR 0.73 [0.50–1.05], P = 0.090). CONCLUSIONS: Vitamin D status is inversely related to type 2 diabetes risk and our data suggest that this association may be partially mediated by subclinical inflammation.